DNA Adductomics by mass tag prelabeling. (5th May 2021) - Wang, Poguang; Roider, Elisabeth; Coulter, Michael E.; Walsh, Christopher A.; Kramer, Caitlin S.; Beuning, Penny J.; Giese, Roger W.
Abstract : Rationale: As a new approach to DNA adductomics, we directly reacted intact, double‐stranded (ds)‐DNA under warm conditions with an alkylating mass tag followed by analysis by liquid chromatography/mass spectrometry. This method is based on the tendency of adducted nucleobases to locally disrupt the DNA structure (forming a "DNA bubble") potentially increasing exposure of their nucleophilic (including active hydrogen) sites for preferential alkylation. Also encouraging this strategy is that the scope of nucleotide excision repair is very broad, and this system primarily recognizes DNA bubbles. Methods: A cationic xylyl (CAX) mass tag with limited nonpolarity was selected to increase the retention of polar adducts in reversed‐phase high‐performance liquid chromatography (HPLC) for more detectability while maintaining resolution. We thereby detected a diversity of DNA adducts (mostly polar) by the following sequence of steps: (1) react DNA at 45°C for 2 h under aqueous conditions with CAX‐B (has a benzyl bromide functional group to label active hydrogen sites) in the presence of triethylamine; (2) remove residual reagents by precipitating and washing the DNA (a convenient step); (3) digest the DNA enzymatically to nucleotides and remove unlabeled nucleotides by nonpolar solid‐phase extraction (also a convenient step); and (4) detect CAX‐labeled, adducted nucleotides by LC/MS 2 or a matrix‐assisted laser desorption/ionization (MALDI)‐MS technique. Results: Examples of the 42 DNA or RNA adducts detected, or tentatively so based on accurate mass and fragmentation data, are as follows: 8‐oxo‐dGMP, ethyl‐dGMP, hydroxyethyl‐dGMP (four isomers, all HPLC‐resolved), uracil‐glycol, apurinic/apyrimidinic sites, benzo[ a ]pyrene‐dGMP, and, for the first time, benzoquinone‐hydroxymethyl‐dCMP. Importantly, these adducts are detected in a single procedure under a single set of conditions. Sensitivity, however, is only defined in a preliminary way, namely the latter adduct seems to be detected at a level of about 4 adducts in 10 9 nucleotides (S/N ~30). Conclusions: CAX‐Prelabeling is an emerging new technique for DNA adductomics, providing polar DNA adductomics in a practical way for the first time. Further study of the method is encouraged to better characterize and extend its performance, especially in scope and sensitivity.